Biogas Production from Sugarcane Vinasse: A Review - Rustiana Yuliasni; Rieke Yuliastuti; Nanik Indah Setianingsih (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
Biogas is a renewable energy sources that could replace the role of fossil fuel. Biogas could be produced from biomass or agro-industrial wastewater. Sugarcane vinasse has potential of biogas production due to its high BOD concentration (10–65 g BOD/l). However, the biogas production from sugarcane vinasse has several drawbacks that hinders the maximum biogas yield, such as: acidic pH (pH 3.5 – 5.0), high temperature (80–90°C) and high concentration of sulfuric acid (> 150 mg/L). Theoretically, the methane potential per gram COD is 0.35 L/gr COD, containing of 60% methane. However, up to date, the maximum biogas production from vinasse was less then its theoretical value. To get the full potential of biogas production from vinasse wastewater as well as to reduce the capital cost for full scale application, combination of suitable pre-treatment, selected microorganisms and bioreactor design-configuration are the most important parameters to be considered. This paper aims to explore the potential of sugarcane vinasse to produce biogas, by elaborating the aforementioned key parameters. In this review the basic characteristic and the potency of sugarcane vinasse wastewater will be elaborated. Furthermore, the effect of key parameters such as pH, temperature, and organic load to biogas production will also be discussed. The biogas technology will also be explored. Lastly, conclusion will be determined